Application of sensitivity analysis in shipyard investment projects - Kaynak, R; Okudan, GE; Guner, M (Wit Press, 2001)
Investing on shipyard and shipbuilding requires considerable amount of expenditure. This expenditure is expected to produce income after the completion of the investment. In general, income is directly proportional to risk. Risk yields either a high income or a loss. Therefore, critical variables, which may have an affect on the investment outcome should be determined, and further analyzed. Sensitivity analysis is one of the tools used for this purpose. This work presents a sensitivity analysis application on inflation rate for a shipyard investment project where inflation values experienced in Turkey over two decades were used.
4th International Conference on Marine Technology -- MAY 23-25, 2001 -- SZCZECIN, POLAND